The Role of Nrf2 in Skeletal Muscle on Exercise Capacity - Yu Kitaoka (MDPI AG, 2021)
Nuclear factor erythroid 2-related factor 2 Nfe2l2 (Nrf2) is believed to play a crucial role in protecting cells against oxidative stress. In addition to its primary function of maintaining redox homeostasis, there is emerging evidence that Nrf2 is also involved in energy metabolism. In this review, we briefly discuss the role of Nrf2 in skeletal muscle metabolism from the perspective of exercise physiology. This article is part of a special issue "Mitochondrial Function, Reactive Oxygen/Nitrogen Species and Skeletal Muscle" edited by Håkan Westerblad and Takashi Yamada.